Model kepemimpinan transformasional dalam manajemen pembiayaan sekolah - Heru Ady Prasetyo; Ngurah Ayu Nyoman M.; Endang Wuryandini (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2021)
This study aims to produce a transformational leadership model design in school financing management. This type of research is Research and Development with 4D steps (Define, Design, Development and Dissemination). The technique of collecting data from interviews, observations, documentation is concluded as factual designs. The development stage of designing a transformational leadership model in school financing management is validated by educational experts and practitioners through Focus Group Discussions (FGD), into internal tested product designs not field tested. The results of preliminary research obtained visualization of the factual model of Top Down leadership in school financing management. The development stage obtained the results of the visualization of transformational leadership models in school financing management. The results of the validation and assessment of the two education experts (FGD) obtained a value of 46 percent of 95.83% of the interpretation of